Farmers’ Knowledge, Perceptions And Management Of The Gall-Forming Wasp, Leptocybe Invasa (Hymenoptera: Eulophidae), On Eucalyptus Species In Uganda - Nyeko, Philip; Mutitu, Eston K.; Day, Roger K. (International Journal of Pest Management, 2007)
Farmers growing Eucalyptus species in Uganda were interviewed using a pre-tested questionnaire to investigate their knowledge, perceptions and management of the Eucalyptus gall-forming wasp, Leptocybe invasa Fisher & LaSalle, with the aim of developing integrated management programme for the pest. Farmers were aware of, and concerned about, the gall problem on Eucalyptus, but the vast majority of them did not know the cause. Most farmers did not attempt to control the infestation because they did not know of suitable control methods and/or the cause of the problem. Farmers' control decisions were not influenced by their experience in cultivating Eucalyptus or their education level. Only 20% of 59 farmers interviewed had received advice on L. invasa, suggesting poor flow of information on tree pests to farmers. Nearly all farmers interviewed still wanted to plant Eucalyptus, and they saw the trees as a source of several products and services. Problems relating to the increasing emergence of alien insect pests in tropical forests, and challenges and strategies for effective management of forest pests in developing countries are discussed.
Keywords: Eucalyptus, indigenous knowledge, Leptocybe invasa, pest management, plantation forestry